The effect of pop up book on 5 – 6 years old children’s listening skill - Anna Khairunnisa (JECCE (Journal of Early Childhood Care and Education), 2021)
Listening skill represents a child’s ability to listen, interpret, understand, and respond to information. The present study aims to find out the effect of pop-up book on listening skills of 5-6 years old kindergarten students in Serang District, Serang City, Banten. To this end, 30 kindergarten teachers in Serang District were recruited to participate in this quantitative survey study. This study found a significant effect of pop-up book on listening skills of children aged 5-6 years old. The significant effect of the pop-up book may be accounted for by its attractive visualization and color, drawing children's attention to understand the story more easily and motivating them to read autonomously. The correlation coefficient of 0.773 indicated a strong relationship between the two variables. In other words, pop-up book in this study positively affect children's listening skill. As the probability score shows s significance level of 0.000 (<0.05), the effect of pop-up book on children's listening skill was deemed significant.